10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
IntroductionAbsence seizures are characterized by the appearance of generalized spike-and-wave complexes (SWCs) on scalp electroencephalography (EEG), but the EEG-level physiological changes that precede the onset of SWCs remain poorly understood. Advances in scalp wide-band EEG have enabled the simultaneous visualization of ultraslow and high-frequency activity, providing an opportunity to examine early ictal dynamics in childhood absence epilepsy (CAE). Here, we report two cases of pediatric CAE in which scalp EEG captured ictal direct current (DC) shifts and ictal high-frequency oscillations (HFOs) within the same seizure epoch.Patients and MethodsWe report two pediatric patients with CAE who exhibited typical absence seizures during hyperventilation-provoked scalp EEG recordings. Across three seizures, the same wide-band EEG methodology enabled the evaluation of ictal DC shifts and HFOs.ResultsAcross three seizures, a reproducible temporal sequence was observed: a negative DC shift emerged several hundred milliseconds before the first SWC, followed by spike-locked HFOs shortly after ictal onset. The DC shift progressively deepened during this interval, whereas HFOs appeared as discrete, band-limited events with modest frequency evolution. Despite differences in seizure duration and clinical background, this pattern was consistent across seizures and between patients.DiscussionThese findings suggest that ictal DC shifts reflect slow network changes preceding thalamocortical hypersynchrony, whereas ictal HFOs index the fast dynamics involved in SWC generation. As both components can be detected noninvasively, scalp wide-band EEG may offer a foundation for developing early ictal biomarkers in CAE.